Length of Methamphetamine Abuse and Sustained Attention Disorders among Methamphetamine Abusers - lyeli Siahjani; mohammad Oraki; hossein zare (Drug Control Headquarters, Research and Education Office, 2013)
Introduction: The aim of this study was to investigate relation between sustained attention disorders and lenght of Methamphetamine abuse. Method: 200 Methamphetamine abusers (males and females) of ages 20-40 who were recruited through residential rehabilitation treatment, selected through random available sampling. To evaluate function of sustained attention Continuous Performance Test was taken and the length of MA abuse gained through demographic information. Data were analyzed by correlation coefficient with SPSS software. Findings: The results show that poor performance in CPT is positively correlated with length of MA abuse. Participants with long MA abuse has less correct response, more commission false and increase in reaction time. Conclusion: Based on these findings, it can be concluded that MA abuse leads to brain damages and cognitive deficits and it is resulting in poor treatment outcomes. Implementing cognitive rehabilitation techniques can increase treatment outcomes.